Replication Stalling at Friedreich's Ataxia (GAA)(n) Repeats In Vivo - Krasilnikova, Maria M. (American Society for Microbiology, 2004)
Friedreich's ataxia (GAA)(n) repeats of various lengths were cloned into a Saccharymyces cerevisiae plasmid, and their effects on DNA replication were analyzed using two-dimensional electrophoresis of replication intermediates. We found that premutation- and disease-size repeats stalled the replication fork progression in vivo, while normal-size repeats did not affect replication. Remarkably, the observed threshold repeat length for replication stalling in yeast (∼40 repeats) closely matched the threshold length for repeat expansion in humans. Further, replication stalling was strikingly orientation dependent, being pronounced only when the repeat's homopurine strand served as the lagging strand template. Finally, it appeared that length polymorphism of the (GAA)(n) · (TTC)(n) repeat in both expansions and contractions drastically increases in the repeat's orientation that is responsible for the replication stalling. These data represent the first direct proof of the effects of (GAA)(n) repeats on DNA replication in vivo. We believe that repeat-caused replication attenuation in vivo is due to triplex formation. The apparent link between the replication stalling and length polymorphism of the repeat points to a new model for the repeat expansion.